Neoliberalism as a real utopia? Karl Polanyi and the theoretical practice of F. A. Hayek - Rodrigues, João (2018)
This article interprets Hayek’s theoretical practice with the help of Polanyi’s framework. Hayek aimed at renewing liberalism after the interwar period, thus helping transforming it into neoliberalism, a real utopia instrumentally concerned with the political and moral economies underpinning markets. The distance between neoliberal theory and practice is less pronounced than it is sometimes assumed. The strength of neoliberalism partially stems from a capacity to articulate an effort to think about real-world mechanisms with an effort to demolish, reconfigure or transform existing structures. Despite his failure to anticipate neoliberalism, Polanyi gives ample intellectual resources to critically interpret the tasks that neoliberals would collectively have to face at the theoretical level, in an epoch of ideological marginality, before their triumphal political deployment at the global level.